Paradigma Pemilihan Kepala Negara di Zaman Khulafa Al-Rasyidin - Sirojuddin Aly (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2005)
In the realm of Political Science, there are various models for selecting leaders of a government. Some involve direct elections, while others rely on representation. Similarly, within Islam, there is diversity in the models of leadership selection. This diversity emerged after the passing of Prophet Muhammad, particularly during the era of the Rashidun Caliphs. This occurred because neither the Quran nor the Hadith provide explicit and detailed instructions regarding the process of selecting a head of state. This article examines the paradigm of leadership selection during the era of the Rashidun Caliphs. It delves into the selection systems for the four caliphs: Abu Bakr, Umar, Uthman, and Ali, each of whom, according to the author, had distinct differences. Furthermore, the article provides a comparative analysis between several modern political systems and the concepts espoused by Islam.